Projeto fuse sensor para melhora da qualidade da continuidade de energia elétrica a partir da diminuição do indicador DEC - Prazeres, Helder Batista de Boa Esperança dos (2024)
The electrical power distribution systems play a crucial role in social well-being and economic development, providing the foundation for essential services and business sus tainability. However, many components of these systems face technological obsolescence, contributing to power supply failures at critical moments. This situation is further exacer bated in Brazil due to the predominance of bare conductors in its distribution networks and the limited presence of underground networks, making them susceptible to failures caused by external factors. It is observed, however, that these failures in the electrical system can take time to be detected and located, leading to a deterioration in power quality, specifically in the system interruption time, which increases the financial compensation paid by utilities to consumers. To address these challenges, this dissertation presents the Fuse Sensor project, developed in partnership with the company SEVEN (Seven Science Systems Ltda), as an innovative solution incorporating the concepts of Smart Grids and IoT (Internet of Things) technology for the faster location and repair of faults, thus enabling improvements in the efficiency and reliability of electrical systems. The Fuse Sensor is designed to meet the present and future needs of the electrical system, focusing on reducing the SAIDI (System Average Interruption Duration Index), and providing significant gains in compensations. The master’s project approach is structured into three distinct stages: in the first stage, the conception and construction of the Fuse Sensor project are presented, along with the testing procedures; in the second stage, validations of the Fuse Sensor project are conducted, including a comparison of the effectiveness of the communication technologies LoRa, SigFox, and FSK; and finally, in the third stage, an economic analysis is carried out, considering not only the acquisition costs of the innovative equipment but also its economic feasibility for the utilities. By addressing these aspects comprehensively, the Fuse Sensor project aims not only to mitigate the repair time of power supply interruptions but also to promote significant improvements in the quality and reliability of the electrical service. Combining technological innovation and detailed economic analysis, the project seeks not only to meet the current demands of the electrical sector but also to pave the way for a more efficient and sustainable future